Clinical evidence of vital pulp therapy in cariously exposed permanent mature teeth : systematic review and meta-analysis - Saldanha, Bernardo Correia Pereira Sales (2018)
Dissertação para obtenção do grau de Mestre no Instituto Universitário Egas Moniz